Significant Feeding Deterrent of Berberine from Tali kuning(Tinospora dissitiflora Diels) Against Two Subterranean Termites Coptotermes formosanus Shiraki and Reticulitermes speratus Kolbe - Wahyudi Wahyudi; Yoshito Ohtani; Hideaki Ichiura (Masyarakat Peneliti Kayu Indonesia, 2012)
Antifeedant activities of berberine isolated from the chloroform fraction of Tali kuning (Tinospora dissitiflora Diels) were evaluated against two subterranean termites, Coptotermes formosanus Shiraki and Reticulitermes speratus Kolbe, respectively. The chloroform fraction of methanol extracts of Tali kuning and authentic berberine chloride were used for comparison. Three replicates and levels of concentrations, 12.5, 25, and 50 mg/ml, respectively, were employed. Filtepapers treated with three chemical substances were used to evaluate the mass losses of the filter paper consumed by the termites, and filter papers treated only with MeOH were used for control. Mass loss (MS), termite mortality (TM) and antifeedant index (AFI) were used to determine the antifeedant variables. The results indicated that regardless of three chemical substances tested, the MS recorded from C. formosanus Shiraki were 2.87 times higher than those of R. speratus Kolbe, and among three levels concentration, 50 mg/ml gave the lowest MS (2.13%). Authentic berberine chloride gave the highest TM (99%), followed by chloroform fraction (88%) and berberine (73%). Interestingly, all antifeedant variables employed in this study gave AFI values less than 20%, indicating significant feeding deterrent activity against two subterranean termites.